The Impact of Transformational Leadership on Digital Transformation Towards Madrasah Reform and Performance - Intan Shella Herdiaty; Anton Wachidin Widjaja (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the pivotal role of transformational leadership in facilitating digital transformation and promoting organizational learning to drive madrasah reform and performance in madrasahs in Indonesia. The research uses a quantitative survey method, the research is limited to madrasahs in Indonesia, engages madrasah leaders, and utilizes SEM-PLS to analyse relationships among variables. The study emphasizes the critical role of transformational leadership in adapting to the digital era and fostering continuous learning, enabling effective madrasah reforms and improved performance. It shows that organizational learning supports digital initiatives, with leaders encouraging adaptation and aligning technology use with academic and religious goals. This research underscores the importance of transformational leadership and organizational learning in driving digital transformation, accelerating institutional reforms, and enhancing performance, particularly in Indonesia's madrasah sector.